Electronic records management in schools: the case study of School Examination Analysis System - Roslin Ab. Hamid; Umi Asma’ Mokhtar; Maryati Mohd. Yusof; Warland, Andrew (Penerbit Universiti Kebangsaan Malaysia, 2019)
Many initiatives have been taken to improve the efficiency of teaching and learning (T&L), administration, and management in schools using various ICT systems. Despite continuous training and exposure to undertake T&L activities and management, comprehensive practices on the principles of electronic records and information management (ERIM) at schools still faced many challenges. This paper presents a proposed framework for ERIM implementation using ICT-based systems in schools incorporating ERIM elements, including ICT skills for teachers, improved ERIM knowledge among teachers, enforcement of policies, acts and guidelines, and continuous training. The paper also discusses a case study finding regarding an ERIM implementation, problems in a School Examination Analysis System (SEAS), ICT skills, knowledge and skills of teachers. This study applies a quantitative approach using a survey technique for data collection. A total of 350 questionnaires were distributed to five Malaysian primary public schools and the response rates are 62.85 percent (220 forms). The study found that almost all teachers have good ICT skills but the knowledge and skills of teachers in ERIM were at a moderate level. Most teachers were unaware of acts, policies and guidelines related to ERIM. This study is expected to assist the Ministry of Education in drafting guidelines for the implementation of ICT based system in schools to enhance the efficacy of T&L, administration and management according to ERIM principles.